2003
DOI: 10.1071/ea01175
|View full text |Cite
|
Sign up to set email alerts
|

Using zero tillage, fertilisers and legume rotations to maintain productivity and soil fertility in opportunity cropping systems on a shallow Vertosol

Abstract: Abstract. The effect of 2 tillage practices (zero v. conventional), fertiliser application (nitrogen, phosphorus and zinc), and pulse-cereal rotation on changes in soil mineral nitrogen, plant-available water in the soil, grain yield and protein, and key soil fertility parameters (total nitrogen, organic carbon) in the Central Highlands of Queensland were examined between 1991 and 1998. Four pasture treatments (perennial legume, perennial grass, annual legume and legume-grass mixes) were included in January 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The variations in the Australian results on the impact of increasing rotation complexity arise from the mix of different practices involved (Blair and Crocker, 2000;Noble et al, 2003;Armstrong et al, 2003;Hulugalle et al, 2007;Bünemann et al, 2008;Hulugalle and Scott, 2008). Here we group rotation complexity into three categories: 1) increased crop diversity (ID) referring to a change from continuous monoculture to continuous rotation, 2) increased cropping frequency (IF), i.e., a change from one crop per year to two or more crops per year (e.g., from continuous wheat to wheat-cotton double cropping), and 3) increased perenniality (IP), i.e., a change from annual crops to a rotation with perennial crops.…”
Section: Crop Systems and Rotationmentioning
confidence: 99%
“…The variations in the Australian results on the impact of increasing rotation complexity arise from the mix of different practices involved (Blair and Crocker, 2000;Noble et al, 2003;Armstrong et al, 2003;Hulugalle et al, 2007;Bünemann et al, 2008;Hulugalle and Scott, 2008). Here we group rotation complexity into three categories: 1) increased crop diversity (ID) referring to a change from continuous monoculture to continuous rotation, 2) increased cropping frequency (IF), i.e., a change from one crop per year to two or more crops per year (e.g., from continuous wheat to wheat-cotton double cropping), and 3) increased perenniality (IP), i.e., a change from annual crops to a rotation with perennial crops.…”
Section: Crop Systems and Rotationmentioning
confidence: 99%
“…Compared to CT, CA is a resource-conserving practice with the potential to increase plant available soil moisture, promote infiltration and reduce the costs of tillage operations (Hobbs et al, 2008;Thomas et al, 2007). Among the most important disadvantages of CA is the increased dependence on herbicides (Armstrong et al, 2003) and that the benefits of CA are realized gradually over long-term (Erenstein, 2003;Giller et al, 2009). Planting basin was also part of this study because conservation tillage with basin has been widely promoted in Southern Africa to be used by resource-poor farmers (Nyamangara et al, 2013) with limited access to draft power.…”
Section: Introductionmentioning
confidence: 99%
“…In Queensland, Australia, zero tillage and no-traffic were observed to minimize environmental degradation effects including soil erosion while increasing grain yield. Further, the amount of rain required to initiate run-off in irrigated cotton was increased by retaining crop residues and other materials that increased soil cover while perennial pasture rotations improved soil fertility (Silburn and Glanville, 2002;Armstrong et al, 2003). Land forming for surface water drainage: Poor drainage is a major problem in Vertisols due to water logging of early planted crops; thus, universally, Vertisols are cropped post-rain season with plant growth being sustained largely by residual soil MC.…”
Section: (B) Soil Fertility Managementmentioning
confidence: 99%
“…Studies in the USA, Australia and Ethiopia indicated that by combining zero, minimum and conservation tillage with rotation cropping improved long-term soil quality and environmental protection including soil erosion control and reduction in land degradation (Lopez-Bellido et al, 1996;Chan et al, 1997;Castano et al, 2000;Nicolova et al, 2001;Morrison and Sanabria, 2002;Guled et al, 2002;Salinas-Garcia et al, 2002;Gupta, 2002;Astatke et al, 2003;Armstrong et al, 2003). Studies on stocking rates in Vertisols in the Ethiopian highlands, conducted between 1996 and 2000, indicated that moderate grazing pressure (stocking rate of 1.8 animal unit months (AUM) ha -1 ) was better than heavy grazing pressure (stocking rate of 3.0 AUM ha -1 ) and removal of grass cover enhanced cracking of the soils.…”
Section: (C) Cropping Systemsmentioning
confidence: 99%